116k views
15 votes
I need help with this please!


I need help with this please! ​-example-1

1 Answer

14 votes

Answer:

Plug in those values for the x in the equations.

Explanation:

f(x) = x^2 + x

(x = -1) :: f(-1) = (-1)^2 + (-1)

f(-1) = -1 + -1

f(-1) = -2

(x = 2) :: f(2) = (2)^2 + (2)

f(2) = 4 + 2

f(2) = 6

f(x) = x^2 - x

(x = -1) :: f(-1) = (-1)^2 - (-1)

f(-1) = 1 - (-1)

f(-1) = 2

(x = 2) :: f(2) = (2)^2 - (2)

f(2) = 4 - 2

f(2) = 2

f(x) = -x^2 - x

(x = -1) :: f(-1) = -(-1)^2 - (-1)

f(-1) = -1 + 1

f(-1) = 0

(x = 2) :: f(2) = -(2)^2 - (2)

f(2) = -4 - 2

f(2) = -6

User Nicoletta
by
5.6k points